1984
DOI: 10.1620/tjem.142.261
|View full text |Cite
|
Sign up to set email alerts
|

Conformational differences between mouse contrapsin and .ALPHA.-1-antitrypsin as studied by ultraviolet absorption and circular dichroism spectroscopy.

Abstract: We have compared the conformation of mouse contrapsin, a novel trypsin inhibitor (Takahara, H. and Sinohara, H. (1982) J. biol. Chem., 257, 2438-2446, and a-l-antitrypsin by UV absorption and CD spectroscopy. The two mouse inhibitors share a similar secondary structure, i.e., 24-29% a-helix, 31% /-sheet, and 10-11% /l-turn. The corresponding values for human a-l-antitrypsin are 48, 25, and 9%, respectively. These results suggest that peptide backbone structures of the two mouse inhibitors resemble each other, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The recombinant Sc-SRP-6-fold was analysed by recording the CD spectrum. The far-UV CD spectra presented a broad negative region in the 208–222 nm range with a minimum peak at 222 nm proceeded by a shoulder at 208 nm (Figure 3B), which is highly similar to that reported for canonical serpins [37]. Based on a deconvoluted spectrum, it was calculated that the Sc-SRP-6 secondary structure contains 15–20% α-helices, 30–35% β-strands, 20–25% β-turns and 23% random coils, which is in agreement with values (22% α-helical and 35% β-strand) predicted by I-TASSER.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The recombinant Sc-SRP-6-fold was analysed by recording the CD spectrum. The far-UV CD spectra presented a broad negative region in the 208–222 nm range with a minimum peak at 222 nm proceeded by a shoulder at 208 nm (Figure 3B), which is highly similar to that reported for canonical serpins [37]. Based on a deconvoluted spectrum, it was calculated that the Sc-SRP-6 secondary structure contains 15–20% α-helices, 30–35% β-strands, 20–25% β-turns and 23% random coils, which is in agreement with values (22% α-helical and 35% β-strand) predicted by I-TASSER.…”
Section: Resultssupporting
confidence: 84%
“…In silico and CD data suggested that recombinant Sc-SRP-6 has an identical fold as the mouse serpin trypsin inhibitor with a composition consisting of 24–29% α-helices, 31% β-sheets, and 10–11% β-turns [37] and of plasminogen activator inhibitor-1, which is composed of 29% α-helices, 19% β-strands, 24% β-turns, and 27% random coils [39] and differs from that of human α-1-antitrypsin, which is composed of 48% α-helices, 25% β-sheets, and 9% β-turns [37].…”
Section: Discussionmentioning
confidence: 99%
“…To test whether pH influences the conformation of the protein we determined the far ultraviolet (UV) circular dichroism spectra of recombinant SRPN6 at different pH. The canonical native serpin fold is composed of a mixture of α-helices, β-sheets, β-turns, and loops, presented as a minimum peak at 222 nm preceded by a shoulder at 208 nm in the far-UV CD spectra [57][59]. The far UV CD spectrum of SRPN6 is highly similar to that of reported serpins (Fig.…”
Section: Resultsmentioning
confidence: 99%